Hermanna Nitscha Teatr Orgii i Misteriów jako powód do zgorszenia? - Wałczyk, Krzysztof (Annales Universitatis Paedagogicae Cracoviensis | Studia de Cultura, 2014)
Hermann Nitsch’s Theatre of Orgy and Mysteries as a reason for scandal? Hermann Nitsch, a representant of the „Viennas Actionism” (germ. Wiener Aktionismus) initiated in the late 1950’s of the XX-century the so called „Theatre of orgy and mystery” (germ. Orgien-Mysterien-Theater). This is a kind of syncretic performance, which combines the elements of the ancient Greek Dionysius feast and Catholic liturgy. The author stages an offering of animals, giving to it the form of religious liturgy. In his ceremonies, the offering ist not meant to be an medium of contact with a higher, divine power, which would result God’s blessing (according to the principle of mutual giving each other). The naturalistically performed rite by Nitsch should help to act out impulsive needs, especially aggression, which has been pushed into the subconscious. The motto of Nitsch’s actions should be: one should be exposed to death in order to experience the spiritual rebirth. It’s highly debatable practice to combine the elements of ancient Greek Dionysius ceremony with the Christian liturgy, as well as to reduce their meaning just to abreaction of biological needs. The contact with higher, divine reality has been here replaced by the naturalistic performance.